What Workers Say: Employee Voice in the Anglo-American Workplace - Adams, Roy J. (Relations industrielles / Industrial Relations, 2008)
What Workers Say: Employee Voice in the Anglo-American Workplace, edited by Richard B. Freeman, Peter Boxall and Peter Haynes, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Human resource management; International; Labor Unions; Polls & surveys; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Unionization; Work environment